Waterproof and water repellent textiles and clothing - Williams, J. (John T.). (Duxford Woodhead Publishing, 2018)
Waterproof and Water Repellent Textiles and Clothing provides systematic coverage of the key types of finishes and high performance materials, from conventional wax and silicone, through controversial, but widely used fluoropolymers and advanced techniques, such as atmospheric plasma deposition and sol-gel technology. The book is an essential resource for all those engaged in garment development, production and finishing, and for academics engaged in research into apparel technology and textile science. Rapid innovation in this field is driving new performance demands in many areas, including the sporting and military sectors. However, another innovation driver is the regulatory framework in the USA, Europe and globally, addressing both health concerns (e.g. with PFOS / PFOA) and environmental impacts (e.g. C8 fluorocarbon finishes). Both of these aspects are fully covered, along with the replacement materials / technologies currently available and under development. In addition, oleophobic and multifunctional coatings are discussed, as are aspects of performance, testing and applications in sportswear, protective clothing, and footwear.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Waterproofing of fabrics; Waterproof clothing; Electronic books